The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fvets.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dark Brooder Rearing and Age on Hypothalamic Vasotocin and Feather Corticosterone Levels in Laying Hens

Abstract: Chickens cannot independently thermoregulate at hatch and lack opportunity to behaviorally thermoregulate with a hen in the egg layer industry, thus barns are heated to thermoneutral temperatures. Dark brooders are low-energy-consuming hot plates, which may be environmentally advantageous while providing welfare-enhancing aspects of maternal care (i.e., shelter and separation of active and inactive individuals). Dark brooder use has been demonstrated to decrease injurious pecking and mortality well into the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…In laying hens, the condition of the plumage and the integument acts as an indicator for feather pecking and cannibalism, both being behavioral disorders caused by various challenges the birds had or have to cope with ( Sepeur et al., 2015 ; Giersberg et al., 2017 ). Recent studies showed that the evaluation of animal welfare in birds may be carried out objectively and noninvasively with the measurement of the stress-related hormone corticosterone in feathers ( Bortolotti et al., 2008 ; Bortolotti et al., 2009 ; Fairhurst et al., 2011 ; Carbajal et al., 2014 ; Ganz et al., 2018 ; Johns et al., 2018 ; Weimer et al., 2018 ; Alba et al., 2019 ; von Eugen et al., 2019 ; Nordquist et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laying hens, the condition of the plumage and the integument acts as an indicator for feather pecking and cannibalism, both being behavioral disorders caused by various challenges the birds had or have to cope with ( Sepeur et al., 2015 ; Giersberg et al., 2017 ). Recent studies showed that the evaluation of animal welfare in birds may be carried out objectively and noninvasively with the measurement of the stress-related hormone corticosterone in feathers ( Bortolotti et al., 2008 ; Bortolotti et al., 2009 ; Fairhurst et al., 2011 ; Carbajal et al., 2014 ; Ganz et al., 2018 ; Johns et al., 2018 ; Weimer et al., 2018 ; Alba et al., 2019 ; von Eugen et al., 2019 ; Nordquist et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies on corticosterone in feathers were performed mostly in wild birds (e.g., Bortolotti et al., 2009 ; Koren et al., 2011 ; Lattin et al., 2011 ; Fairhurst et al., 2012 ; Lendvai et al., 2013 ; Harms et al., 2015 ; Kouwenberg et al., 2016 ; Aharon-Rotman et al., 2017 ; Freeman and Newman, 2018 ; Monclús et al., 2020 ), using feather corticosterone as a retrospective view on challenges the birds had to cope with during feather growth. Despite the wild birds, results of first investigations in poultry ( Berkvens, 2012 ; Carbajal et al., 2014 ; Jenni-Eiermann et al., 2015 ; Zeinstra et al., 2015 ; Johns et al., 2017 ; Weimer et al., 2018 ; Alba et al., 2019 ; von Eugen et al., 2019 ; Nordquist et al., 2020 ; Lindenwald and Rautenschlein, unpublished data) are also encouraging; however, in the absence of a standardized procedure, authors applied different methods to detect and quantify corticosterone in feathers. These variations, such as variations in the amount of feather material or methanol volume for the extraction, crushed vs. grind up feathers, and different methods for filtration or different assays, make it rather impossible to compare the results, properly ( Romero and Fairhurst, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that stress hormones like CORT in birds or cortisol in humans and other mammalian animals are important for the body's ability to respond to stress and injury. They are known to have complex effects on the skeleton, with small amounts needed for normal bone development but large amounts inhibiting bone growth (61). The finding of increased cumulative CORT deposition with age was similarly established in another recent chicken study (62).…”
Section: Discussionmentioning
confidence: 64%
“…It is known that, for example, rearing with a foster hen can lead to morphological changes such as differences in cell soma size in the hippocampus of the adult hens' brain ( Nordquist et al., 2013 ). Besides, rearing with a foster hen or dark breeder rearing have an influence on the hypothalamic dopaminergic and vasotinergic system and the corticosterone level in feathers ( Hewlett et al., 2020 , Nordquist et al., 2020 ). But these findings describe rather an altered brain development and cannot be transferred to our hens because they were reared together 16 wks after hatching.…”
Section: Discussionmentioning
confidence: 99%